Desenvolvimento farmacotécnico e avaliação da qualidade e estabilidade da formulação em gel de dicloridrato de clorexidina de liberação prolongada - Thiago Abilio Lopes Rocha (2015)
The current work involved the development of a controlled release system of chlorhexidine dihydrochloride (CxC) complexed with betacyclodextrin (CD) in the molar ratio (1:1). Through this incremental innovation approach, it was possible to increase the solubility of the active in water. The complex CxC:CD formation was evidenced by solubility tests and in the infrared spectrophotometry. Based on the technical, regulatory and commercial rationality, inexpensive excipients, with defined pharmacotechnical functions and within their usual concentrations were used form a gel matrix. Standardized and reproducible production process for obtaining a drug- cyclodextrin compound and the final formulation were obtained in a manner scalable to make them in an industrial environment. The evaluation of the stability of the product was executed for six months under three conditions of temperature and humidity by quantifying the level of chlorhexidine dihydrochloride, p-chloroaniline limit (impurity), physical assessments, pH values and microbiological results. The gel remained stable in two of three conditions (25°C±2°C/ 60%±5%RU and 5°C±3°C). In the most drastic condition (40°C±2°C/ 75%±5%RU) there was a decrease in the level of CxC in the T6°month. All others parameters remained within its specifications, including the impurity. These results demonstrated good stabilization provided by cyclodextrin and the possibility of further studies such as long-term (30°C±2°C/ 75%±5%RU for 24 months) with this binary composition or higher proportions.